2005
DOI: 10.1002/cbic.200400108
|View full text |Cite
|
Sign up to set email alerts
|

From the Insoluble Dye Indirubin towards Highly Active, Soluble CDK2‐Inhibitors

Abstract: In search of novel antitumor therapies. The natural product indirubin (1) is one of the class of indigo dyes, insoluble in aqueous systems, employed by mankind since the Bronze Age for textile coloring. In 1999 indirubin was reported to be a modest inhibitor of the enzyme CDK2, a key target in the ongoing search for novel antitumor therapies. With the guidance of X‐ray structures, indirubin was transformed to yield novel, soluble, almost colorless, highly potent CDK2 inhibitors that strongly inhibit the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 24 publications
2
79
0
Order By: Relevance
“…In particular, numerous modifications have been carried out on positions 3 0 , 5 0 , 6 0 on one indole ring and 5 or 6 on the other indole ring (Hoessel et al, 1999;Leclerc et al, 2001;Meijer et al, 2003;Merz et al, 2004;Polychronopoulos et al, 2004;Jautelat et al, 2005). However, no modifications have ever been reported on position 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, numerous modifications have been carried out on positions 3 0 , 5 0 , 6 0 on one indole ring and 5 or 6 on the other indole ring (Hoessel et al, 1999;Leclerc et al, 2001;Meijer et al, 2003;Merz et al, 2004;Polychronopoulos et al, 2004;Jautelat et al, 2005). However, no modifications have ever been reported on position 7.…”
Section: Discussionmentioning
confidence: 99%
“…This approach first revealed that Aurora A-C, FMS-like tyrosine kinase 3 (FLT3), RET constitute new targets of IO, 5BIO and 6BIO. Vascular endothelial growth factor receptor (VEGF-R) had been previously described as a target for indirubins (Jautelat et al, 2005). The selectivity panel also revealed that, compared to the three other indirubins, 7BIO is a poor kinase inhibitor.…”
Section: Different Bromoindirubins Display Different Selectivities Fomentioning
confidence: 99%
“…Indirubin and particularly indirubin derivatives such as indirubin-3 0 -monoxime and indirubin-5-sulfonate, which have low toxicity, have been considered as anticancer agents (Hoessel et al, 1999). Indirubin and its derivatives have been described as selective inhibitors of cyclin-dependent kinases (CDKs) such as CDK1/ cyclin B, CDK2/cyclin A, CDK2/cyclin E and CDK5/ p25 (Hoessel et al, 1999;Davies et al, 2001;Marko et al, 2001;Jautelat et al, 2005). It has been reported that these compounds are able to inhibit the proliferation of a variety of cultured cell types by a block in the G1/S or the G2/M phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Except for two, all have the indolone lactam group bound to the gk+1 and gk+3 residues. 60 There is one structure of CSNK1 kinase that shows the NH and carbonyl of the lactam pointed toward the hinge but has the molecule flipped 180°so the carbonyl is facing the gatekeeper region while the N(H) is close to the gk+3 NH. It is quite possible that this structure is bound in a different tautomeric form.…”
mentioning
confidence: 99%